Estimation of Thermal Contact Conductance Between Blank and Tool Surface in Hot Stamping Process - Zahari, Taha (2015)
In hot stamping, the determination of the thermal contact conductance values between the blank and tool surface during the process is crucial for the purpose of simulating the blank rapid cooling inside the tool using finite element analysis (FEA). The thermal contact conductance value represents the coefficient of the heat transfer at the surface of two solid bodies in contact and is known to be influenced greatly by the applied pressure. In order to estimate the value and its dependency on applied pressure, the process of hot stamping was replicated and simplified into a process of compression of heated flat blank in between the tool at different applied pressure. The temperature of the blank and tool surface were measured by means of thermocouples installed inside the tool. Based on the measured temperature, the thermal contact conductance between the surfaces was calculated using Newton’s cooling law equation. The calculated value was then used to simulate the blank cooling inside the tool using FEA commercial software. This paper describes an experimental approach to estimate the thermal contact conductance between a blank made of Boron Steel (USIBOR 1500) and tool made of Tool Steel (STAVAX). Its dependency on applied pressure is also studied and the experimental results were then compared with FEA simulations.